A continental-wide molecular approach unraveling mtDNA diversity and geographic distribution of the Neotropical genus Hoplias - Cardoso, Yamila Paula (2018)
With an estimate of around 9,000 species, the Neotropical region hosts the greatest diver- sity of freshwater fishes of the world. Genetic surveys have the potential to unravel isolated and unique lineages and may result in the identification of undescribed species, accelerating the cataloguing of extant biodiversity. In this paper, molecular diversity within the valuable and widespread Neotropical genus Hoplias was assessed by means of DNA Barcoding. The geographic coverage spanned 40 degrees of latitude from French Guiana to Argentina. Our analyses revealed 22 mitochondrial lineages fully supported by means of Barcode Index Number, Automatic Barcode Gap Discovery and phylogenetic analyses. This mtDNA survey revealed the existence of 15 fully supported mitochondrial lineages within the once considered to be the continentally distributed H. malabaricus. Only four of them are currently described as valid species however, leaving 11 mitochondrial lineages currently masked within this species complex. Mean genetic divergence was 13.1%. Barcoding gap analysis discriminated 20 out of the 22 lineages tested. Phylogenetic analyses showed that all taxo- nomically recognized species form monophyletic groups. Hoplias malabaricus sensu stricto clustered within a large clade, excluding the representatives of the La Plata River Basin. In the H. lacerdae group, all species but H. curupira showed a cohesive match between taxo- nomic and molecular identification. Two different genetic lineages were recovered for H. aimara. Given the unexpected hidden mitochondrial diversity within H. malabaricus, the COI sequence composition of specimens from Suriname (the type locality), identified as H. mala- baricus sensu stricto, is of major importance.